Hubungan Pengetahuan, Gizi, Sikap terhadap Kesehatan Remaja Khususnya Anemia - Nurhidayati, Riesky Budi (MPI Press, 2024)
Background: The World Health Organization states that more than 30% of the world's population suffers from anemia. The prevalence of anemia in adolescent girls in Indonesia in 2018, namely in the group of adolescents aged 11-14 years was 13.5% and aged 15-21 years was 29.5%.Objective: To determine the relationship between knowledge, nutrition and attitudes towards adolescent health, especially anemia in Bojonggede in 2022.Method: The method used in the research is quantitative with analytical descriptive research and uses a Cross-Sectional design, where the research is carried out when collecting data between the independent variable and the dependent variable which is carried out together at the same time, with a population size of 134 respondents , the sample in this study was 57 teenage respondents selected using the Probability Sampling technique. The instrument used in collecting data in this research was a questionnaire sheet. Data analysis using Chi-square.Results: Chi-Square test results for the relationship between knowledge and anemia p-value, namely p-value = 0.000 < 0.05 and Chi-Square test results for the relationship between nutrition and anemia, namely 0.000 < 0.05, as well as the relationship between attitudes and anemia in adolescents p-value = 0.017 < 0.05. Conclusion: There is a relationship between knowledge, nutrition and attitudes towards adolescent health, especially anemia.